PERANCANGAN CORPORATE IDENTITY SWEET VILLY - FAJRA DHANY, Dr. M. Nasrul Kamal, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Sweet Villy is a trademark created by The young entrepreneur named Ovilly Angnesia located at St. Tomat 21 Tangah Jua, Bukittinggi. Sweet Villy not Have corporate identity as a logo in the form of corporate identity.  The logo is the first thing to remember by the consumer of a product as well as a distinctive identity with  competitor in similar fields. Sweet Villy want to introduce products to consumers more broadly, but yes not yet have a corporate identity to distinguish it from competitors which is an obstacle if you want to introduce  the product to the consumer.The research method that I use is the qualitative method, while in the data analysis the authors use  analytical methods 5W + 1H (what, where, who, why, when, how). The design of the logo Sweet Villy  primarily as an initial identity trademark applied into the manual book. The main media used in the design of this logo is a media Sweet Villy manual book. Then the supporting media such as aprons, x-banners, posters,  stickers, pins, open closed sign, business cards, t-shirts, packaging, Instagram feed.Keywords: Logo, Sweet Villy, Identity.